Sino-Russian relations: The implications of Putin's strategic folly" - Kurtis H. Simpson (Centre for International Governance Innovation (CIGI), 2023)
Sino-Russian relations have changed dramatically over the past decade, especially following Russia's invasion of Ukraine on February 24, 2022, and its ongoing occupation. The success of Canada's national Indo-Pacific strategy depends on a comprehensive understanding of China, Russia and the ties that bind these strategic partners. Their relationship has not always been smooth, fluctuating from shared ideologies, mutual aid and support to deep divisions and open conflict. Their Cold War-era rivalry evolved into a more balanced partnership after the collapse of the Soviet Union in 1991 as they joined forces to counter US global dominance. But the ties between the two countries began to unravel following Russian President Vladimir Putin's decision to invade Ukraine, isolating Russia economically and diplomatically and undermining its military power to the point where China now considers it "a junior partner.
Keywords: 330